Application Of AKHLAK Culture As A Mediation Variable Of Workload And Work Environment On Organizational Commitment (Study On Non-Permanent Employees Of BNI Pare-Pare Branch) - Ni Putu, Indah Permata Dewi (Scientium Management Review, 2022)
Organizational commitment is the force binding individuals to perform an action that is relevant to one or more goals. This study aims to analyze the effect of workload and work environment on the organizational commitment of non-permanent employees of BNI Pare-Pare Branch, either directly or indirectly by using AKHLAK Culture as a mediating variable. This type of research is quantitative research involving 115 respondents to fill out a questionnaire with the results of data processed using SmartPLS 4. Based on the results of data processing and discussion, the conclusion of this study is that when the workload of employees decreases, it does not affect the increase in organizational commitment of BNI Pare-Pare Branch employees, both directly and when AKHLAK Culture is used as a mediating variable. Furthermore, a conducive and comfortable work environment has a significant direct effect on increasing organizational commitment from employees but when it is associated with AKHLAK Culture as a mediating variable, the indirect effect shown has not shown a significant impact.